2020
DOI: 10.1186/s43093-020-00023-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic variables on industrial output in one of the world’s fastest-growing countries: case evidence from India

Abstract: Increase in industrial output is an important indicator to identify the socioeconomic development of a nation. India is one of the fastest-growing economies in the world; using its comparative advantage and capitalizing its educated youths, it tries to be as a hub of manufacturing in the world map. Under these circumstances, the present study attempts to identify the effects of dynamic macroeconomic variables on manufacturing output in India using secondary data from 1990Q1 to 2017Q4 sourced from the World Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The result suggests that gross capital formation is helpful in increasing the gross value added of industries in India. Sankaran et al (2020) also observed the significant contribution of gross fixed capital formation to industrial development in India. The regression coefficient of per person emoluments with gross value added of industries was positive and statistically significant.…”
Section: Rationality Of Regression Coefficientmentioning
confidence: 83%
See 4 more Smart Citations
“…The result suggests that gross capital formation is helpful in increasing the gross value added of industries in India. Sankaran et al (2020) also observed the significant contribution of gross fixed capital formation to industrial development in India. The regression coefficient of per person emoluments with gross value added of industries was positive and statistically significant.…”
Section: Rationality Of Regression Coefficientmentioning
confidence: 83%
“…Thampy and Tiwary (2021) have examined the association of the local banking sector and human capital with the development of the manufacturing sector. Sankaran et al (2020) have identified the impact of macro-economic variables on manufacturing output in India using national-level data. Finally, taking a broader view, Maroof et al (2019) have assessed the determinants of industrial development in South Asian countries, and Singh, Singh, and Ashraf (2020) have examined the impact of STDI, IPPI and SEDI on manufacturing value added in 41 developed and developing countries.…”
Section: Journal Of Social Economics Researchmentioning
confidence: 99%
See 3 more Smart Citations